Microbial Dynamics in a Musalais Wine Fermentation: A Metagenomic Study - Yongzeng Pei; Mengrong Chen; Qiling Chen (Foods)
This study provides a comprehensive analysis of the microbial dynamics involved in the fermentation process of traditional Musalais wine, an intangible cultural heritage of Xinjiang. Utilizing metagenomic sequencing, we identified 2894 microbial species, of which 494 persisted throughout the fermentation process. Saccharomyces cerevisiae was the dominant species, with its prevalence increasing from 97.35% in the early phase to 99.38% in the mid phase, before slightly decreasing to 98.79% in the late phase. Additionally, 24 non-Saccharomyces yeast species, including Hanseniaspora uvarum, Lachancea thermotolerans, and Torulaspora delbrueckii, were detected. Common species associated with other fermented foods, including Wickerhamomyces anomalus, Kluyveromyces marxianus, Saccharomyces eubayanus, and Zygosaccharomyces parabailii, were also identified. Notably, species not previously used in food fermentation, such as Saccharomyces jurei, Sodiomyces alkalinus, Vanrija pseudolonga, and Moesziomyces antarcticus, were also identified in this study. Furthermore, the Kyoto Encyclopedia of Genes and Genomes (KO) and Gene Ontology (GO) revealed notable variations in metabolic pathways and enriched functional genes. In addition, a total of 82 volatile compounds were detected in the final product, with higher alcohols (60.12%), esters (37.80%), and organic acids (1.80%) being the most prevalent. These results offer important insights into microbial interactions and their influence on Musalais wine quality, laying the groundwork for optimizing the fermentation process.